Styloid process phenotype and atheromatous plaque: Radiographic and bone density assessment in parathyroid disease - Adilia Mirela Pereira Lima Cid; Davi de Sá Cavalcante; Marcela Lima Gurgel; Ana Carolina Saraiva; Ana Alicia Sales Ricardo; Lúcio Mitsuo Kurita; Paulo Goberlânio de Barros Silva; Catarina Brasil d’Alva; Ana Rosa Pinto Quidute; Fabio Wildson Gurgel Costa (Journal of Oral Biology and Craniofacial Research)
Purpose: This study aimed to assess the styloid process (TBSP) phenotype and to identify suggestive images of calcified atheromatous plaques (CAP) in panoramic radiographs of patients with primary hyperparathyroidism (PHPT) and post-surgical hypoparathyroidism (hypoPT). Additionally, it aimed to analyze the association between the bone mineral status of patients with parathyroid diseases and the radiographic findings. Material and methods: A cross-sectional case-control study was conducted with individuals diagnosed with PHPT (n = 25) and post-surgical hypoPT (n = 25). A control group (n = 50) comprised individuals without parathyroid gland disorders. Panoramic radiographs were utilized for both quantitative (length) and qualitative (mineralization patterns) evaluation of the TBSP, as well as for assessing the prevalence of CAP. Results: The frequency of TBSP exceeding 30 mm was significantly higher in the PHPT and post-surgical hypoPT groups compared to the control group. CAP occurred more frequently in the PHPT group. Cases of low bone mineral density (BMD) were associated with PHPT. In the PHPT group, low BMD was linked to an increased average TBSP length (p = 0.025) and a higher frequency of elongated TBSP (p = 0.022). Multivariate analysis revealed an inverse relationship between the T-score of the femoral neck and TBSP length in the PHPT group (p = 0.028). Conclusions: Compared to the control group, individuals with PHPT and post-surgical hypoPT showed distinct imaging findings related to TBSP and CAP. Individuals with PHPT and low BMD showed a higher frequency of elongated TBSP.